Hydrothermal Synthesis of Chloride Free Nitrogen Doped TiO2 Nanoparticles - Prodjosantoso, A.K.; Wibowo, H.; Kusumawardani, C. (Asian Journal of Chemistry, 2018)
In this work, the synthesis and characterization of chloride free nitrogen doped TiO2 nanoparticles have been undertaken. The chloride-free nitrogen doped TiO2 nanoparticles were hydrothermally prepared by mixing acidic ethylene diamine solution with titanium tetraisopropoxide followed by heating at 120 and 150 ºC for 12 h and 180 ºC for 6 h. The resulted solid was isolated, dried, grinded and calcined at 450 ºC for 3 h. The samples were characterized using powder X-ray diffraction, UV-visible reflectance and SEM-EDAX methods. The results indicated that the samples consist of a major component of rutile and minor anatase types. The hydrothermal temperature does not affect to the composition of the product. The N-doped in TiO2 decreases the lattice parameters. The crystallite size of rutile is somewhat bigger than anatase. As expected, all samples are free of chloride.